An alternative view at the zero-bias anomaly of metallic point contacts - Gloos, Kurt (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2009)
We have studied the zero-bias anomaly of point contacts as function of contact size for a wide range of materials from simple normal metals, superconductors, and magnets to highly correlated heavy-fermion compounds. The size dR of the zero-bias anomaly varied in a universal manner proportional to the square ofthe contact resistance R between 1 W and 10 kW, that is for contact radii from about 15 nm down to 0.2 nm. Magnetic impurities, two-level systems, or a tunneling barrier are unlikely to be the main source of thisanomaly. We suggest instead Kondo-type scattering of the conduction electrons due to a spontaneous electronspin polarization at the point contact.